Managing the cascading risks of droughts: institutional adaptation in transboundary rivers - Garrick, D; Schlager, E; De Stefano, L; Villamayor-Tomas, S (American Geophysical Union, 2018)
Transboundary river basins experience complex coordination challenges during droughts. The multi‐scale nature of drought creates potential for spillovers when upstream adaptation decisions have cascading impacts on downstream regions. This paper extends the institutional analysis and development (IAD) framework to examine drought adaptation decision‐making in a multi‐jurisdictional context. We integrate concepts of risk management into the IAD framework to characterise drought across its natural and human dimensions. A global map identifies regions where severe droughts combine with institutional fragmentation to require coordinated adaptation. We apply the risk‐based IAD framework to examine drought adaptation in the Rio Bravo/Grande – an archetypical transboundary river shared by the US and Mexico and by multiple states within each country. The analysis draws on primary data and a questionnaire with fifty water managers in four distinct, yet inter‐linked, ‘institutional catchments’, which vary in terms of their drought characteristics, socio‐economic attributes and governance arrangements. The results highlight the heterogeneity of droughts and uneven distribution of their impacts due to the interplay of drought hazards and institutional complexity. Transboundary water sharing agreements influence the types and sequence of interactions between upstream and downstream jurisdictions, which we describe as spillovers that involve both conflict and cooperation. Interdependent jurisdictions often draw on informal decision‐making venues (e.g. data sharing, operational decisions) due to the higher transaction costs and uncertainty associated with courts and planning processes, yet existing coordination and conflict resolution venues have proven insufficient for severe, sustained droughts. Observatories will be needed to measure and manage the cascading risks of drought.